Pengaruh Penerapan Model Pembelajaran Kooperatif dengan Strategi Think Talk Write terhadap Kemampuan Penalaran, dan Komunikasi matematis, serta Motivasi Belajar Siswa dalam Pembelajaran Matematika di SMPN 1 Sinjai Utara - Arsyad, Nurdin; Asdar; K, Muthmainnah (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2018)
This research aims to determine the influence of implementing the think talk write (TTW) strategy of cooperative learning model towards mathematics reasoning and communication abilities and students motivation in mathematics learning. The type of this research was a quasi-experimental study involving two different treatment groups. The population of this study were students of grade VII SMPN 1 Sinjai Utara and selected by cluster random sampling that were class VII-6 and VII-7. The results obtained from descriptive statistical analysis was: the mathematics reasoning abilities of students by applying cooperative learning model with TTW strategy is in low category, communication ability is in moderate category, and student learning motivation is in moderate category, and the mathematics reasoning abilities of students by applying direct learning model with expository strategy is in very low category, communication ability is in low, and student learning motivation is in moderate category. The results of inferential statistical analysis obtained that: mathematical reasoning, and communication ability, and the motivation of students by applying cooperative learning model with TTW strategy better than the mathematical reasoning, and communication ability, and the learning motivation of students taught by direct learning model. From the result of this research, it can be concluded that there was the influence of applying cooperative learning model with think talk write strategy to mathematical reasoning, and communication ability, and the learning motivation of students.